PENGARUH PELATIHAN EMPATI MELALUI KARTU EMOSI TERHADAP HASIL PEMBELAJARAN PERKEMBANGAN SOSIAL EMOSIONAL ANAK PRASEKOLAH - Annisa Wigati Rozifa; Awwalul Wiladatil Qodliyah (JOMIS (Journal of Midwifery Science), 2025)
Improving children's social-emotional abilities requires using play methods. One of the visual media in the playing process is picture cards. Picture cards are a game tool that is used to help children understand learning so that learning activities are expected to be interesting and fun. This research aims to determine the effect of empathy training through emotion cards on learning outcomes for the social and emotional development of preschool children. This research design uses a Quasi-Experimental design with a pretest-posttest with a control design. In this study, there is one experimental group and one control group that will be measured before and after the experimental treatment is given. This research was conducted in the 'Aisyiyah Jombang Branch Work Area, namely at 'Aisyiyah Bustanul Athfal 1 Jombang and 'Aisyiyah Bustanul Athfal 3 Jombang Kindergartens. The research will be conducted from September 2023 to January 2024. The population in this study is all preschool children aged 5-6 years at Kindergarten 'Aisyiyah Bustanul Athfal 1 Jombang and 'Aisyiyah Bustanul Athfal 3 with a total of 53 people. The sampling technique in this research was purposive random sampling so that a sample of 50 people was obtained, and then divided into 2 (intervention group and control group). The instrument used was a questionnaire. Based on the results of statistical analysis, there is an influence of empathy training through emotion cards on the learning outcomes of preschool children's social-emotional development.